The legacy of Liberalism, Community and Culture - Sardoč, Mitja (Dve domovini, 2016)
This article introduces the thematic section of Two Homelands celebrating the 25th anniversary of the publication of Will Kymlicka%s Liberalism, Community and Culture, one of the seminal books on multiculturalism and contemporary political theory in general. It contextualizes this symposium thematic section by identifying some of the assumptions that the then-existing liberal conceptions of justice were based upon when addressing issues related to cultural diversity. At the same time, it summarizes the argument for cultural rights advanced by Kymlicka in Liberalism, Community and Culture. It then presents the papers that are part of this symposium thematic section and their contribution to the understanding the liberal conception of multiculturalism has had on all subsequent theorizing over cultural diversity and civic equality. 5400 aDediščina knjige Liberalism, Community, and CultuaThis article introduces the thematic section of Two Homelands celebrating the 25th anniversary of the publication of Will Kymlicka%s Liberalism, Community and Culture, one of the seminal books on multiculturalism and contemporary political theory in general. It contextualizes this symposium thematic section by identifying some of the assumptions that the then-existing liberal conceptions of justice were based upon when addressing issues related to cultural diversity. At the same time, it summarizes the argument for cultural rights advanced by Kymlicka in Liberalism, Community and Culture. It then presents the papers that are part of this symposium thematic section and their contribution to the understanding the liberal conception of multiculturalism has had on all subsequent theorizing over cultural diversity and civic equality.
Keywords: civic equality; cultural rights; državljanska enakost; kulturne pravice; Kymlicka, Will; liberalism; liberalizem; multiculturalism; multikulturalizem; večkulturnost